Antidepressant Effect of Sodium Butyrate is Accompanied by Brain Epigenetic Modulation in Rats Subjected to Early or Late Life Stress - Valvassori, Samira S.; Varela, Roger Bitencourt; Resende, Wilson Rodrigues; Possamai-Della, Taise; Borba, Laura d. A.; Behenck, João Paulo; Réus, Gislaine Zilli; Quevedo, João (Current Neurovascular Research, 2023)
Background: Major depression has a complex and multifactorial etiology constituted by the interaction between genetic and environmental factors in its development. Objective: The aim of this study was to evaluate the effects of sodium butyrate (SD) on epigenetic enzyme alterations in rats subjected to animal models of depression induced by maternal deprivation (MD) or chronic mild stress (CMS). Methods: To induce MD, male Wistar rats were deprived of maternal care during the first 10 days of life. To induce CMS, rats were subjected to the CMS for 40 days. Adult rats were then treated with daily injections of SD for 7 days. Animals were subjected to the forced swimming test (FST), and then, histone deacetylase (HDAC), histone acetyltransferase (HAT), and DNA methyltransferase (DNMT) activities were evaluated in the brain. Results: MD and CMS increased immobility time in FST and increased HDAC and DNMT activity in the animal brains. SD reversed increased immobility induced by both animal models and the alterations in HDAC and DNMT activities. There was a positive correlation between enzyme activities and immobility time for both models. HDAC and DNMT activities also presented a positive correlation between themselves. Conclusion: These results suggest that epigenetics can play an important role in major depression pathophysiology triggered by early or late life stress and its treatment.
Keywords: chronic mild stress